Quasi-isotropic analysis of anisotropic thin films on optical waveguides - Horvath, Robert (Langmuir : the ACS journal of surfaces and colloids, 2007)
Thin films assembled on a substrate are often anisotropic. Nevertheless, because of experimental limitations, sufficient parameters to characterize the anisotropy, even in the simplest (and perhaps most common) case of uniaxial thin films, which are birefringent, are not usually available. This paper examines the consequences of treating them as isotropic thin films, with particular reference to their characterization via perturbation of the propagation constants (effective refractive indices) of optical waveguides. It is shown that the refractive index and geometrical thickness of a thin film thus calculated are often unrealistic (especially when the thin film is positively birefringent), but the mass per unit area may be quite precise, depending on the sign and magnitude of the birefringence